2018
DOI: 10.1002/cctc.201800363
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Cobalt Oxide Based Nanoarray Catalysts with Hierarchical Architectures: In Situ Raman Spectroscopy Investigation on the Carbon Monoxide Reaction Mechanism

Abstract: Herein, a facile strategy for the in situ growth of a Co3O4‐based precursor with unique hierarchical architectures oriented diagonal or perpendicular to Ni surfaces is reported. This strategy to prepare grafted ZIF‐67@Co3O4 and MOF‐199@Co3O4 precursor structures is based on a simple hydrothermal synthesis method to obtain the Co3O4 precursor and the subsequent in situ growth of ZIF‐67 and MOF‐199, respectively. The morphologies of the Co3O4 products can be tailored by controlling the solvent polarity and conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 56 publications
6
19
0
Order By: Relevance
“…For α-MnO2, the asymmetrical reduction peak manifests that the main reduction steps are processed together in the range of 200-370 °C. In addition, the α-MnO2@Co3O4 sample profile displays complex reduction peaks occurring at the range of 120-380 °C, attributed to the reduction process of Co3O4 [26,27]. It can be clearly observed that the reduction peaks of α-MnO2@Co3O4 shift toward lower temperatures in comparison to those of pure α-MnO2 and Co3O4-b (Fig.…”
Section: Redox Behavior and Surface Chemical States Analysesmentioning
confidence: 90%
“…For α-MnO2, the asymmetrical reduction peak manifests that the main reduction steps are processed together in the range of 200-370 °C. In addition, the α-MnO2@Co3O4 sample profile displays complex reduction peaks occurring at the range of 120-380 °C, attributed to the reduction process of Co3O4 [26,27]. It can be clearly observed that the reduction peaks of α-MnO2@Co3O4 shift toward lower temperatures in comparison to those of pure α-MnO2 and Co3O4-b (Fig.…”
Section: Redox Behavior and Surface Chemical States Analysesmentioning
confidence: 90%
“…At present, there are many technical methods for controlling volatile organic compounds (VOCs), such as adsorption, catalytic oxidation, combustion, plasma, and so on. Among them, catalytic oxidation is known as the most efficient and economical method to remove VOCs [10][11][12][13][14]. Besides, catalytic oxidation has also been recognized as a promising technology for reducing exhaust gases because it directly converts pollutions into CO 2 and H 2 O at relatively lower temperatures and reduces the production of other atmospheric pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] Additionally, the four pronounced characteristic peaks for CuCoO x synthesized from the rGO/CuCoO x hybrids are unequivocally ascertained at 231.64, 256.18, 332.21, and 686.69 cm −1 and are in good agreement with previous reports. [ 25–27 ] From the above discussions, we conclude that optimized hydrothermal growth and binary solvent formulation for inkjet printing enables fabrication of rGO/CuCoO x gas sensors with high material uniformity.…”
Section: Resultsmentioning
confidence: 93%